Expanding manganese(iv) aqueous chemistry: unusually stable water-soluble hexahydrazide clathrochelate complexes - Shylin, Sergii I.; Pogrebetsky, James L.; Husak, Alina O.; Bykov, Dmytro; Mokhir, Andriy; Hampel, Frank; Shova, Sergiu; Ozarowski, Andrew; Gumienna-Kontecka, Elzbieta; Fritsky, Igor O. (Chemical Communications, 2021)
Mn cage complexes are rare, and the ones successfully isolated in the solid state are not stable in water and organic solvents. Herein, we present the first report of mononuclear Mn clathrochelates, in which the encapsulated metal exists in the oxidation state +4. The complexes are extremely stable in the crystalline state and in solutions and show rich redox chemistry.
CRIS-Team WoS Importer:2021-10-15